Developing and validating the educational materials for a nurse-led self-management education in adults with type 2 diabetes - Azami, Golnaz; Soh, Kim Lam; Shariff Ghazali, Sazlina; Md. Said, Salmiah; Aazami, Sanaz; Mozafari, Mosayeb; Taghinejad, Hamid; Badakhsh, Behzad (S. Karger AG, 2019)
Background: Diabetes education and self-care are the cornerstones of diabetes management. There are few nurse-led structured diabetes management programs available in Iran.Objectives: This paper aims to develop and validate a nurse-led diabetes self-management intervention for patients with type 2 diabetes. Method: The theoretical framework underpinning the intervention was the Bandura’s selfefficacy theory. The seven basic steps of the Taba model were used to develop and validate the study intervention. Results: The preliminary results from this study suggest that the study intervention was carefully contextualized and linked to the existing diabetes care. Overall, the intervention was very well received and appreciated by the respondents.Conclusion: This was the first known validated nurse-led diabetes self-management intervention available in the Persian Language.